Subparaneural Versus Circumferential Extraneural Injection at the Bifurcation Level in Ultrasound-Guided Popliteal Sciatic Nerve Blocks: A Prospective, Randomized, Double-Blind Study. Issue 4 (1st July 2014) - Choquet, Olivier; Brault Noble, Guillaume; Abbal, Bertrand; Morau, Didier; Bringuier, Sophie; Capdevila, Xavier
Abstract : Background: The ideal spread of local anesthetic for effective, rapid, and safe sciatic nerve block is debated. We hypothesized that subparaneural ultrasound-guided injection results in faster onset and has a better success rate than extraneural circumferential spread. Methods: Patients undergoing elective tibial, foot, and ankle surgery with popliteal sciatic nerve blocks were prospectively enrolled. After randomization, the needle tip position was adjusted to ensure circumferential extraneural or subparaneural spread; 0.3 mL/kg of mepivacaine 10 mg/mL was injected. Post hoc video analysis was used to group the patients according to extraneural, subparaneural, and unintentional intraepineural spread. Results: There were 26 (43.3%) patients in the subparaneural group and 22 (36.7%) in the extraneural group. Block onset time was shorter in the subparaneural group than in the extraneural group (11 [3–21] minutes; mean [95% confidence interval], 11 [8.97–13.02] minutes and 17 [6–30] minutes; mean [95% confidence interval] 18.37 [14.17–22.57] minutes, respectively; P = 0.002). The duration of sensory blockade increased (397 [178–505] minutes vs 265 [113–525] minutes; P = 0.04). The success rate of the block also increased. Unintentional intraepineural injection occurred in 8% of patients (3 patients in the subparaneural group and 1 patient in the extraneural group; NS). Block onset time was shorter than for the subparaneural and extraneural groups (6 [3–12] minutes, 12 [3–21] minutes, and 18 [6–30] minutes; P = 0.01). Conclusions: A subparaneural injection accelerated the onset time and increased the duration of tibial nerve sensory blockade compared with circumferential extraneural injection. With unintentional intraepineural spread, the onset time was significantly shorter than for the other groups.